2014
DOI: 10.1177/0004867414536931
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic polypharmacy in schizophrenia patients in China and its association with treatment satisfaction and quality of life: Findings of the third national survey on use of psychotropic medications in China

Abstract: APP was found in about one in three schizophrenia patients. The prevalence of APP seems to have been increasing since 2002. Considering the increased frequency of drug-induced side effects and the patients' and their relatives' dissatisfaction with antipsychotic treatment, further examination of the rationale and appropriateness of APP and its alternatives is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 45 publications
1
36
2
Order By: Relevance
“…In a series survey, the frequency of polypharmacy significantly increased from 26.1% (2002) and 26.4% (2006) to 34.2% in 2012 (P < 0.001) in China. 26 The data analysis in that study revealed that polypharmacy-administered patients and their families had lower satisfaction with treatment, higher mental quality of life, earlier onset age, more side-effects, and higher antipsychotic doses; the patients were also more likely to receive first-generation antipsychotics, but less likely to receive benzodiazepines.…”
Section: Discussionmentioning
confidence: 93%
“…In a series survey, the frequency of polypharmacy significantly increased from 26.1% (2002) and 26.4% (2006) to 34.2% in 2012 (P < 0.001) in China. 26 The data analysis in that study revealed that polypharmacy-administered patients and their families had lower satisfaction with treatment, higher mental quality of life, earlier onset age, more side-effects, and higher antipsychotic doses; the patients were also more likely to receive first-generation antipsychotics, but less likely to receive benzodiazepines.…”
Section: Discussionmentioning
confidence: 93%
“…haloperidol, chlorpromazine, lithium carbonate) 17 . According to a recent Chinese study, the reduced availability of therapeutic classes can potentially be associated with polypharmacy utilization 38 . The updated RENAME did not include antipsychotic agents, but did include two anti-parkinson drugs (cabergoline and Cad.…”
Section: Tablementioning
confidence: 99%
“…With the rediscovery of clozapine (CLO),29,30 SGAs, which combined potent (5HT2A) serotonergic blockade with potent but “fast-off” dopamine D2 blockade, were developed. The range of therapeutic indications was broadened, and there was a progressive shift from a paternalistic behavioral control of SMI symptoms to a more patient-centered approach, which valued improved psychosocial functioning and quality of life 31–33. Since the early 2000s, the development of antipsychotics with partial agonism at dopamine D2 receptors has led several authors to speak of a class of “third-generation” antipsychotics 34.…”
Section: Introductionmentioning
confidence: 99%